Preparation and properties of multi-branched poly(D-lactide) derived from polyglycidol and its stereocomplex blends - A. Petchsuk; S. Buchatip; W. Supmak; M. Opaprakasit; P. Opaprakasit (eXPRESS Polymer Letters, 2014)
Multi-branched poly(D-lactide)s (mbPDLAs) with various structures are synthesized via ring-opening polymerization by using polyglycidol (PG) macro-initiators. Their chemical structures and thermal properties are controlled by adjusting feed ratios of D-lactide (DLA) and PG. The materials are blended with commercial linear poly(L-lactide)(l-PLLA) to form a stereocomplex structure. Effects of mbPDLAs structures and l-PLLA/mbPDLA ratios on the blends’ thermal, mechanical, and rheological properties are evaluated. Mechanical properties of the stereocomplex blends, especially elongation at break and toughness, are dependent on the blend compositions, in which a 90:10 ratio exhibits the most desirable properties. The material also exhibits the lowest complex viscosity, which provides easy processing conditions. This is achieved by the incorporation of copolymers with multi-branched structures and an ability to form a much stronger stereocomplex structure.